Broadband Dielectric Spectroscopy with a Microwave Ablation Antenna - Klementina Vidjak; Carolin Hessinger; Marta Cavagnaro (Sensors, 2023)
Microwave ablation is a technique used to treat tumorous tissue. Its clinical use has been greatly expanding in the last few years. Because the design of the ablation antenna and the success of the treatment greatly depend on the accurate knowledge of the dielectric properties of the tissue being treated, it is highly valuable to have a microwave ablation antenna that is also able to perform in-situ dielectric spectroscopy. In this work, an open-ended coaxial slot ablation antenna design operating at 5.8 GHz is adopted from previous work, and its sensing abilities and limitations are investigated in respect of the dimensions of the material under test. Numerical simulations were performed to investigate the functionality of the floating sleeve of the antenna and to find the optimal de-embedding model and calibration option for obtaining accurate dielectric properties of the area of interest. Results show that, as in the case of the open-ended coaxial probe, the accuracy of the measurement greatly depends on the likeness between the calibration standards’ dielectric properties and the material under test. Finally, the results of this paper clarify to which extent the antenna can be used to measure dielectric properties and paves the way to future improvements and the introduction of this functionality into microwave thermal ablation treatments.